A note on the flowtime network restoration problem. (2nd December 2021) - Cohen, Yaarit Miriam; Keskinocak, Pinar; Pereira, Jordi
Abstract: The flowtime network restoration problem was introduced by Averbakh and Pereira (2012 ) who presented a Minimum Spanning Tree heuristic, two local search procedures, and an exact branch-and-bound algorithm. This note corrects the computational results in Averbakh and Pereira (2012 ).